Skin Lesions as a Presenting Feature of Dimorphic T-Lymphoblastic Leukemia in an Adolescent Male. Issue 4 (16th May 2023) - Chapman, Stacy; Almiski, Muhamad; Marko, Daniel; Sekiguchi, Debora; Dawson, AJ; Keijzer, Richard; Fromm, Jonathan; Israels, Sara J.
Abstract : Cutaneous involvement is rare in acute lymphoblastic leukemia/lymphoma, particularly within the T-cell lineage. Review of the literature for cutaneous involvement in T-cell lymphoblastic lymphoma/leukemia identifies mostly case reports, with the majority of cases involving adults. We describe an adolescent male presenting with cervical lymphadenopathy and skin lesions leading to a diagnosis of early T-cell precursor lymphoblastic leukemia. Unique to this case is the age of the patient, presence of a dimorphic blast population, and the skin lesions preceding other signs of disease by at least 1 month.